Recent progress of artificial cells in structure design, functionality and the prospects in food biotechnology - Li Li; Xiaolin Yao; Guoliang Li; Qianqian Guo; Juan Yue; Wenguang Liu; Yapeng Fang; Adam Midgley; Mouming Zhao; Katsuyoshi Nishinari (Materials Today Bio)
Artificial cells have bridged the gap between non-living systems and biological cells. In recent years, artificial cells designed to simulate cellular structure and function have garnered significant attention. These artificial cells demonstrate vast potential for advancements in various biomedical areas, including simulating cell structure and function, creating innovative biosensors, facilitating bioactives transport, enabling micro and nanoreactors, and improving the targeted therapy for chronic foodborne diseases. In the interdisciplinary field of artificial cell construction, based on their constituent components, these systems can be categorized into lipid/polymer vesicles, coacervate, colloidosome, and metal-organic framework (MOF) artificial cells. They are anticipated to significantly enhance advancements in food science, particularly in cellular structure optimization, precise nutrition delivery, targeted nutrient release, and rapid detection methods. Consequently, this paper will comprehensively cover the historical background, fabrication techniques, and structural characteristics of artificial cells. From a functional design perspective, this review examines the growth and division mechanisms, energy production processes, encapsulation and reaction vessels, carriers, and information exchange systems of artificial cells. Ultimately, it provides a comprehensive evaluation of the safety of artificial cells from both biological and environmental viewpoints, to introduce and expand the application scenarios of this innovative biotechnology in food science.